2021
DOI: 10.1111/liv.14798
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and MRI features of combined hepatocellular‐cholangiocarcinoma in patients with or without cirrhosis

Abstract: Background and Aims Differences in combined hepatocellular‐cholangiocarcinomas (cHCC‐CCAs) arising in high‐risk patients with or without liver cirrhosis have not been elucidated. This study aimed to compare the clinicopathologic and imaging characteristics of cHCC‐CCAs in patients with or without cirrhosis and to determine the prognostic factors for recurrence‐free survival (RFS) after curative resections of single cHCC‐CCAs. Methods This retrospective study included 113 patients with surgically resected singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
6
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
6
6
3
Order By: Relevance
“…Some researchers remarked on the predictive significance of LNM [ 23 , 37 , 39 , 42 ]. Nevertheless, the same finding was not obtained in our study, supported by several previous studies [ 14 , 50 , 51 ]. Possible reasons that can explain this contradiction are shown as follows: Firstly, due to the highly heterogeneous nature, the predominance of HCC or ICC component may affect the biological behavior of the tumor [ 41 , 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…Some researchers remarked on the predictive significance of LNM [ 23 , 37 , 39 , 42 ]. Nevertheless, the same finding was not obtained in our study, supported by several previous studies [ 14 , 50 , 51 ]. Possible reasons that can explain this contradiction are shown as follows: Firstly, due to the highly heterogeneous nature, the predominance of HCC or ICC component may affect the biological behavior of the tumor [ 41 , 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results had better sensitivity in the LR-5 category at the cost of reduced specificity than that of the previous studies (6,12,18,19), which showed a range of sensitivity between 55.2 and 74%.…”
Section: Lrcategorycontrasting
confidence: 74%
“…According to the previous study by Wang et al (23) with the 2010 WHO classification, more cHCC-CCAs were misclassified 19) with cHCC-CCA in patients with cirrhosis, the rate classified as LR-M in cHCC-CCAs was decreased (58.8% vs 53%). The rate classified as LR-M in cHCC-CCAs was also even lower than that of recent studies (14,19,23) in patients at risk. That could explain why LI-RADS v2018 showed decreased specificity in the diagnosis of HCCs than recent reports with LI-RADS v2014 (21) and v2017 (4).…”
Section: Lrcategorycontrasting
confidence: 72%
See 1 more Smart Citation
“…18,19 In previous studies of surgically resected cHCC-CCAs, patients with cHCC-CCA categorized as LR-M had a worse prognosis than those categorized as LR-4 or 5. 20,21 Our results, using iCCA with curative surgery, also showed that patients with iCCA categorized as LR-M had significantly worse RFS than those categorized as LR-4 or 5. Additionally, the LR-M category was an independent factor for postsurgical outcomes of HCC, cHCC-CCA, and iCCA in each study, including the present study.…”
Section: Discussionsupporting
confidence: 54%